Convergencia y desarrollo en la Argentina urbana (2003–2016). Issue 1 (1st March 2021) - González, Fernando Antonio Ignacio; Santos, Maria Emma; London, Silvia
Abstract: This article analyses the recent evolution of territorial disparities in Argentina, measured by a Multidimensional Poverty Index, by carrying out a formal convergence analysis between agglomerates. In particular, the existence of absolute β-convergence and σ-convergence is tested. The information comes from the microdata of the Permanent Household Survey. The results suggest that, although an end-to-end analysis of the period shows a decrease in poverty accompanied by a reduction in territorial disparities between the main urban agglomerates in Argentina, when disaggregating by subperiods, it is evident that in periods of economic growth (essentially from 2003 to 2009), territorial disparities increased. Conversely, in periods of stagnation, these disparities decrease. Resumen: Este articulo analiza la evolución reciente de las disparidades territoriales en Argentina, medida por un Índice de Pobreza Multidimensional, mediante un análisis formal de convergencia entre aglomerados. En particular, se testea la existencia de convergencia-β absoluta y convergencia-σ. La información proviene de los microdatos de la Encuesta Permanente de Hogares. Los resultados sugieren que, si bien en un análisis punta-a-punta del período se observa una reducción de la pobreza acompañada de una reducción de las disparidades territoriales entre los principales aglomerados urbanos de Argentina, al desagregar por subperíodos, se evidencia que en los períodos de crecimiento económico (esencialmente del 2003 al 2009) se incrementaron las disparidades territoriales. En tanto que en los periodos de estancamiento, estas disparidades se redujeron. Résumé: Ce travail analyse l'évolution récente des disparités territoriales en Argentine, mesurée à partir d'un Indice multidimensionnel de la pauvreté, sur la base d'une étude de la convergence entre les agglomérations urbaines. Il teste en particulier l'existence de la beta convergence absolue et de la sigma convergence. Les informations proviennent de microdonnées de l'Enquête permanente des ménages. Bien qu'une analyse ponctuelle de la période montre une réduction générale de la pauvreté accompagnée d'une réduction des disparités territoriales entre les principales agglomérations urbaines d'Argentine, la désagrégation par sous-périodes permet d'observer que pendant les périodes de croissance économique (essentiellement de 2003 à 2009), les disparités territoriales se sont accrues alors qu'en période de stagnation elles se sont réduites.